Estudo da Influencia de antioxidantes na avaliação da estabilidade oxidativa de biodiesel pelo método petroOXY - Silva, Gustavo Bezerra (2015)
The use of biodiesel as a total or partial substitute for petroleum diesel is significant, however their low oxidative stability is a favorable point. Therefore the use of antioxidants to increase the time of degradation by oxidation is promoted feasible. However, the antioxidant action is related to the chemical composition of biodiesel which is added. Considering the importance and growth of the biodiesel industry, their need for use of antioxidants, and search for new sources as raw materials, it is necessary to study the efficiency of antioxidants to increase the life of biodiesel, and to evaluate new cultures with production potential as jatropha (Jatropha curcas L.) and radish (Raphanus sativus L.). The objective of this study was to test the antioxidant BHT, PA and PG in concentration of 50, 200, 500, 1000 and 2000 mg / kg in biodiesel jatropha, turnip and soy, employing PetroOXY methodology, accelerated oxidation test for the determination of its induction period. The biodiesel was obtained through transesterification reactions using methyl route, with yields higher than 80% and were characterized by some physical and chemical parameters. The use of antioxidant was observed to increase the life of biodiesel and the concentration there is an increased induction time. The efficiency of BHT was always increasing with increasing concentration of biodiesel while for all PG and PA was a decrease of efficiency in higher concentration. The methodology used to evaluate oxidative stability, PetroOXY, was effective, good repeatability and reproducibility, as well as being faster and completes the Rancimat method. At higher concentration of 2000 mg / kg, the best performance was for BHT in concentrations lower than 2000 mg / kg, the efficiency was better for the PA-PG, the three studied biodiesel, soybean, radish and jatropha